Analysis and design of resonance Raman reporter molecules by density functional theory. (1st August 2017) - Mu, Xijiao; Guo, Yonghong; Li, Yulong; Wang, Zhong; Li, Yuee; Xu, Shuhong
Abstract : Resonance Raman (RR) probe is a new biomarker technology, which has the characteristics of low detection limit and being capable of multiple detection. In this paper, through analyzing the UV–Vis spectra, non‐resonant and pre‐resonant Raman spectra of Azobenzene‐based RR probe (Am‐CN Azo‐OH) and Azobenzene using density functional theory (DFT), we try to explore common rules for designing new RR probes. First, the excitation wavelength is a prerequisite for intense enhancement which should match the absorption spectrum of RR probe; second, each vibration mode presents quite different resonance enhancement; finally, the highest resonance enhancement is derived from the vibration of the atomic groups around the chromophore, which coincides with the nature transition orbit (NTO) theory of the strongest excited state of the molecule. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The resonance enhancement effect of the Raman spectrum is the strongest near the UV–Vis absorption peak, and the resonance enhancement for each vibration mode is not equal. The excitation wavelength is a prerequisite for intense enhancement which should match the absorption spectrum of RR probe. Each vibration mode presents quite different resonance enhancement. The highest resonance enhancement is derived from the vibration of the atomic groups around the chromophore.